2008
DOI: 10.5483/bmbrep.2008.41.1.079
|View full text |Cite
|
Sign up to set email alerts
|

Verticillium dahliae toxins-induced nitric oxide production in Arabidopsis is major dependent on nitrate reductase

Abstract: The source of nitric oxide (NO) in plants is unclear and it has been reported NO can be produced by nitric oxide synthase (NOS) like enzymes and by nitrate reductase (NR). Here we used wild-type, Atnos1 mutant and nia1, nia2 NR-deficient mutant plants of Arabidopsis thaliana to investigate the potential source of NO production in response to Verticillium dahliae toxins (VD-toxins). The results revealed that NO production is much higher in wild-type and Atnos1 mutant than in nia1, nia2 NR-deficient mutants. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 41 publications
2
37
1
1
Order By: Relevance
“…tabaci the NR NO-generated mechanism increased plant resistance. A similar trend of response was observed in Verticillium dahliae infection in arabidopsis (Shi and Li, 2008). Yamamoto-Katou et al (2006) showed that silencing NR leads to reduced levels of NO in response to elicitin.…”
Section: Nitric Oxide In Plant Defencesupporting
confidence: 70%
“…tabaci the NR NO-generated mechanism increased plant resistance. A similar trend of response was observed in Verticillium dahliae infection in arabidopsis (Shi and Li, 2008). Yamamoto-Katou et al (2006) showed that silencing NR leads to reduced levels of NO in response to elicitin.…”
Section: Nitric Oxide In Plant Defencesupporting
confidence: 70%
“…Moreover, although there is an abundant literature documenting the lower accumulation and/or detection of NO in Atnoa1 (20,22,24,79,80), there are also reports showing that Atnoa1 is not always impaired in NO accumulation. For example, in response to H 2 O 2 , to iron, to indole 3-butyric acid, to Verticillium dahliae toxins, or to zeatin, NO production is as high in Atnoa1 as in wild type plants (23,41,42,81,82). The presence of a nitrite-dependent NO production pathway in Atnoa1 might account for those conflicting observations.…”
Section: Tablementioning
confidence: 99%
“…This led to the renaming of AtNOS1 as NO-associated protein 1 (AtNOA1) (25). Nevertheless, publications still refer to AtNOS/A1 as a potential NOS (41,42). Here, we examined the ability of AtNOS1 protein to bind and oxidize arginine into NO, using several independent assays.…”
mentioning
confidence: 99%
“…20 The wild-type and nia1, nia2 NR-deficient mutants of Arabidopsis were used to visualize microtubules in living leaf cells. The results showed that VD-toxins induced a timedependent microtubule depolymerization, and that microtubule depolymerization was more severe in WT than in nia1, nia2 NRdeficient mutants, especially at the later stages (Fig.…”
Section: No and H 2 O 2 Modulates Vd-toxins-induced Dynamic Microtubumentioning
confidence: 99%